PEMBERDAYAAN PEREMPUAN SEBAGAI SOLUSI PENCEGAHAN RADIKALISME - Kurniawati, Nurul Qolbi (Jurnal Moderasi, 2023)
Abstract The act of radicalism and terrorism under the name of ethnic, religion and gender are becoming rampant. The new motive was targeting woman, to be the subject of the violence. However, the term woman and radicalism itself have several paradoxes in its discourses. As oppose that woman might be both the subject and object of violence, they could also actively and collectively prevent the radicalism. thus, there should be enough generalization of woman as the weak target of radicalism and terrorism. Woman are crucial in the contribution of radicalism prevention. This research intended to seek the complicity of woman in terrorism movement. It revealed the reasons behind many acts of terrorism that had happened. Moreover, this research alsooffer solutions to empower women  to prevent radicalism  served several facts of woman abilities that were actively and collectively contributed in radicalism prevention. Keywords: Women, Radicalism Movement